Mother-offspring interactions in Zebu cattle - da Costa, M. J. R. Paranhos [UNESP]; Schmidek, A. [UNESP]; Toledo, L. M. (Blackwell Publishing, 2008)
The knowledge of the interaction between mother and offspring might contribute to enhance the welfare of the offspring and to improve the reproductive efficiency of the cow. However, there is still little information available about such interaction in some cattle breeds. A series of observational studies were set up, addressing the mother-offspring relationships of Nelore, Guzerat and Gyr cattle breeds. Firstly, the behaviour of cows and calves around the time of parturition was described, and then, the underlying factors that affect the calves' survival and development were studied. Special attention was given to the failure or delay in the first suckling. The results together are indicative of genetic variability for some studied variables, indicating the possibility of selection for calf vigour (using latency to stand up and latency to suckle as its indicators) and maternal ability (using percentage of time in contact with the calves), in spite of the estimates of heritability were low and presented high standard deviation for all variables. The individual variability in their suckling behaviour and the efficiency in first suckling cannot be explained by a single isolated underlying factor. By now, there are some results available, although there are many questions without answers. The field is still open for the development of future research.